TOURISM AND AFRO-RELIGIOUS PRACTICES IN PROTECTED AREAS: a confrontational relationship? - dos Santos Júnior, Valdevino José; Saldanha Machado, Carlos José; Machado Vilani, Rodrigo (RITUR - Revista Iberoamericana de Turismo, 2021)
Protected areas (PAs) in Brazil are used to carry out activities such as scientific research, environmental education, recreation, ecotourism and for religious purposes. However, Afro-religious practices are often seen as incompatible with the public use of PAs and confrontational with tourist activity. Thus, this article aims to deconstruct the existence of a conflict between tourism and Afro-religious practices and declare that PAs are a democratic space for public use. From an anthropological perspective, the methodology stands out as a qualitative research, a case study with secondary and bibliographical data collection. Tijuca National Park and Pedra Branca State Park were selected for the analysis of this article. By analyzing their forest management plans, we realize that Afro-religious practices are considered polluting and degrading for the environment and could also affect the scenic beauty and tourist activities of the PAs. However, it is known that Afro-religious people have an intrinsic relationship with nature, since African divinities are inseparable from nature. The PAs are territorially protected public spaces where multiple uses must be ensured, so both tourists and Afro-religious people should be equally respected. Although PAs have been a stage for conflicts, they can be democratic spaces, where justice, equality and religious freedom must prevail. For this purpose, it is extremely important to make real progress in environmental public policies, to transmute the ignorance of conservatism, prejudice, intolerance, and environmental racism still present in Brazil. It would be useful an inclusive look at Afro-religious and tourist practices in PAs in order to help in the construction of democratic public policies, sharing the environment without limitations, considering, and valuing the vision of the Afro community, ensuring Afro-religious freedom, and deconstructing the idea of ​​an opposition between the two activities.